Analysis of physicochemical components and antioxidants of four kinds of Guizhou honey - LIU, Min; DENG, Weixi; ZHANG, Hongli; WU, Yihua; WANG, Lunxin; FAN, Ying (Food Science and Technology, 2023)
The physicochemical profile composition of four different types of honey samples and their antioxidant activity were analyzed. The physicochemical properties, including fructose, glucose, sucrose, total phenols (TP), flavonoids, insoluble matter, 5-hydroxymethylfurfural (5-HMF), amylase, sucrase, and 17 amino acids, and antioxidant power, were determined in four kinds of honey from Guizhou. The results showed significant differences in the physicochemical composition and antioxidant power of different honey samples. Among them, compared with other honey samples, Coptis chinensis Franc honey showed more TP and total phenolic content and a stronger antioxidant capacity. The correlation analysis showed that 5-HMF was negatively correlated with antioxidant indicators, TP, flavonoids, and multiple amino acids, implying that 5-HMF may affect the quality and biological activity of honey. Various amino acids were significantly correlated with antioxidant activity, TP, and flavonoids. Principal component analysis revealed that multiple amino acids played a major role in the first principal component (PC1), which may suggest that amino acids are an important factor in the quality of honey. Taken together, these findings provide a reference for further research on honey quality from different sources and its associated health effects.